“Securing Digital Footprints: The Emerging Necessity of Digital Estate Planning” - Agarwal, Yuvika (Trinity Law Review, 2025)
The procedures and resources for handling a person’s digital assets, such as social media profiles, digital data, and online accounts, are all included in digital estate planning. This study describes digital estate planning, classifies its several forms, and emphasises how important it is becoming in the current digital era. This study compares and contrasts the legal systems in India and the United States that oversee digital estate planning. It explores the idea of “digital inheritance,” describing how recipients get digital assets. The study also examines the legality of electronic wills, or “e-wills,” discussing present legal uncertainties as well as possible future developments. Lastly, it talks about digital estate management technology and offers helpful advice on how to manage digital legacies efficiently, maintain security, and make digital estate migrations easier.
Keywords: Digital assets; inheri tance; Legality; E-wills; Technology; Suggestions